Implementasi Elemen Difusi Inovasi Rogers dalam Kegiatan Sosialisasi Literasi oleh Dinas Perpustakaan dan Kearsipan Kota Pasuruan - Julyansyah, Deady Suryadilaga; Sunarya, Aris (Soetomo Magister Ilmu Administrasi, 2023)
Rogers' Innovation Diffusion refers to a theory that explains how innovations are accepted and adopted by society. It encompasses innovation types, communication channels, implementation timing, and social support. This theory is crucial in analyzing the adoption of innovations in literacy socialization activities such as the "Kulitmas" and "Koplingmas" Programs. The aim of "Koplingmas" is to provide literacy access through mobile libraries, enhance reading interest, and provide direct education through engaging activities. "Kulitmas" aims to boost reading interest by involving the community in interactive events, introducing local culture, and engaging the public in library-based literacy within the city environment. The research problem statement and objectives are to describe the innovations, analyze the implementation of Rogers' Innovation Diffusion elements, and identify inhibiting and driving factors within the "Kulitmas" and "Koplingmas" Programs. This research could offer insights to enhance literacy program strategies and library management. The research methodology employed is qualitative with a descriptive approach. Data collection involves interviews, observations, and document analysis related to the "Kulitmas" and "Koplingmas" Programs. Analysis is conducted based on Rogers' four Innovation Diffusion elements to comprehend innovation implementation and influencing factors. The study reveals that the "Kulitmas" and "Koplingmas" Programs effectively enhance reading interest and literacy awareness. The implementation of Rogers' innovation diffusion is evident through diverse communication channels, appropriate timing management, and support from educational institutions and communities. Driving factors include positive community responses to modern communication, strong collaboration, and implementation flexibility. However, resource and technological constraints act as barriers, which can be overcome through strategic adaptation approaches and cross-sectoral support. These findings provide guidance for improving and developing more effective literacy programs. Keywords: Rogers' Innovation Diffusion Elements; Literacy Socialization ; Library and Archives Department